Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's find the 20th term ([tex]\(a_{20}\)[/tex]) of an arithmetic progression (AP) given the first term ([tex]\(a = 10\)[/tex]) and the common difference ([tex]\(d = -3\)[/tex]).
In an arithmetic progression, the [tex]\(n\)[/tex]-th term ([tex]\(a_n\)[/tex]) can be calculated using the formula:
[tex]\[ a_n = a + (n - 1) \cdot d \][/tex]
Here:
- [tex]\(a\)[/tex] is the first term.
- [tex]\(d\)[/tex] is the common difference.
- [tex]\(n\)[/tex] is the term number.
- [tex]\(a_n\)[/tex] is the [tex]\(n\)[/tex]-th term we want to find.
We need to find the 20th term ([tex]\(a_{20}\)[/tex]), so [tex]\(n = 20\)[/tex].
Let's substitute the values into the formula:
[tex]\[ a_{20} = a + (20 - 1) \cdot d \][/tex]
Firstly, calculate [tex]\(20 - 1\)[/tex]:
[tex]\[ 20 - 1 = 19 \][/tex]
Now, substitute [tex]\(a = 10\)[/tex] and [tex]\(d = -3\)[/tex]:
[tex]\[ a_{20} = 10 + 19 \cdot (-3) \][/tex]
Next, calculate the product [tex]\(19 \cdot (-3)\)[/tex]:
[tex]\[ 19 \cdot (-3) = -57 \][/tex]
Finally, add this result to the first term [tex]\(a = 10\)[/tex]:
[tex]\[ a_{20} = 10 + (-57) \][/tex]
[tex]\[ a_{20} = 10 - 57 \][/tex]
[tex]\[ a_{20} = -47 \][/tex]
So, the 20th term [tex]\(a_{20}\)[/tex] of the arithmetic progression is [tex]\(-47\)[/tex].
In an arithmetic progression, the [tex]\(n\)[/tex]-th term ([tex]\(a_n\)[/tex]) can be calculated using the formula:
[tex]\[ a_n = a + (n - 1) \cdot d \][/tex]
Here:
- [tex]\(a\)[/tex] is the first term.
- [tex]\(d\)[/tex] is the common difference.
- [tex]\(n\)[/tex] is the term number.
- [tex]\(a_n\)[/tex] is the [tex]\(n\)[/tex]-th term we want to find.
We need to find the 20th term ([tex]\(a_{20}\)[/tex]), so [tex]\(n = 20\)[/tex].
Let's substitute the values into the formula:
[tex]\[ a_{20} = a + (20 - 1) \cdot d \][/tex]
Firstly, calculate [tex]\(20 - 1\)[/tex]:
[tex]\[ 20 - 1 = 19 \][/tex]
Now, substitute [tex]\(a = 10\)[/tex] and [tex]\(d = -3\)[/tex]:
[tex]\[ a_{20} = 10 + 19 \cdot (-3) \][/tex]
Next, calculate the product [tex]\(19 \cdot (-3)\)[/tex]:
[tex]\[ 19 \cdot (-3) = -57 \][/tex]
Finally, add this result to the first term [tex]\(a = 10\)[/tex]:
[tex]\[ a_{20} = 10 + (-57) \][/tex]
[tex]\[ a_{20} = 10 - 57 \][/tex]
[tex]\[ a_{20} = -47 \][/tex]
So, the 20th term [tex]\(a_{20}\)[/tex] of the arithmetic progression is [tex]\(-47\)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.